(untitled) (Academia Science Repository, 2023)
The present-day volumes of diverse facets in the area of second language learning and teaching are implemented from a unique collection of reviews produced by national native’s educational organizations in the United Kingdom. The most proficient promotion in the use of a second or later learned language, as Naring, G., Briel, M., & Brouwers, A. (2006) claim, may be attributed to numerous educational factors. One of the foremost reasons underlining the fact that the “United Kingdom portrait of language education policies and practices is exceedingly dominant is that English is indigenous language” (Nias, J. 1996). This case study is supposed to contribute with diverse theories of the United Kingdom innovative language education practices to language teaching areas of examination. Also, “linguistic teaching and learning methods vary across degrees, different types of curriculum structures and functions in linguistics” (Morrison, N. 2015).